Participatory land use planning in Nairambi subcounty- Empowering communities for sustainable development - Nangendo, G.; Kyasiimire, B.; Opige, M.; Ssemmanda, R. (Ecological Trends Alliance, 2021)
Of the 7571 hectares administrated by Nairambi subcounty, Buvuma district, Uganda, 37% was assigned to oil palm cultivation, with 29% declared as protected forests. This leaves local communities with hard choices about how to meet their needs from the remaining 34% of the land. Ecological Trends Alliance, supported by Tropenbos International, worked with three of the five parishes that make up Nairambi subcounty to achieve food security and sustainable land management through a new land use plan. This was developed through dialogue and participatory processes with communities in each parish to ensure that the plan promoted inclusive decision making and monitoring. This infobrief presents the vision, goal and objectives identified by communities to move the subcounty towards more sustainable land use, and outlines the main issues and recommendations to address these challenges.